Fossil fuels and clean, plentiful energy in the 21st century: The example of coal - Mark Jaccard (EIB Papers, 2007)
Many people believe we must quickly wean ourselves from fossil fuels to save the planet from environmental catastrophe, wars and economic collapse. However, we have the technological capability to use fossil fuels without emitting climate-threatening greenhouse gases or other pollutants. The natural transition from conventional oil and gas to unconventional oil, unconventional gas and coal for producing electricity, hydrogen and cleaner-burning fuels will decrease energy dependence on politically unstable regions. In addition, our vast fossil fuel resources, perhaps especially coal, are likely to remain among the cheapest sources of clean energy for the next century and perhaps longer, which is critical for the economic and social development of the worlds poorer countries. By buying time for increasing energy efficiency, developing renewable energy technologies and making nuclear power more attractive, fossil fuels will play a key role in humanitys quest for a sustainable energy system.
Keywords: 330